Surgical ligation of A Large Mastoid Emissary Vein in A Patient Complaining of Pulsatile Tinnitus - Kim, Su Geun (J Int Adv Otol, 2021)
Pulsatile tinnitus is an uncommon symptom characterized by a perceived sound pulsing like a heartbeat. Here, we report an unusual case of a patient with unilateral pulsatile tinnitus caused by a large, prominent mastoid emissary vein (MEV). A 45-year-old woman presented at our hospital with pulsatile tinnitus. She had persistent tinnitus for 20 years, and her symptoms had worsened in the previous 2 years. She said that she perceived a sound pulsing like a heartbeat. She had some hearing impairment in both the ears for a long time owing to long-term otitis media. The temporal bone computed tomography scan showed a large right jugular bulb, and there was a large MEV canal draining into the right sigmoid sinus. Therefore, we decided to perform a large MEV ligation with the planned right tympanoplasty. On follow-up, the patient’s pulsatile tinnitus improved completely. According to reviews, this is the first reported case of surgical ligation of a large MEV as a treatment for pulsatile tinnitus; therefore, we report this case with a brief literature review.